Dietary ecology of the common sun skink Eutropis multifasciatus (Kuhl, 1820) in Thua Thien-Hue province, Viet Nam - Chung, Ngo Dac; Binh, Ngo Van; Truong Thi, Nguyen Thi (Academia Journal of Biology, 2015)
Eutropis multifasciatus (Kuhl, 1820) is a common species in Vietnam, the knowledge of ecology of this terrestrial viviparous skink is still poorly known. In this study, we focused on the feeding ecology of E. multifasciatus to understand spatial, temporal, and sexual variations in the dietary composition of E. multifasciatus. A total of 323 food items, viz. 288 animal items and 29 plant items were found in 176 stomachs of skinks. The most numerous prey items of E. multifasciatus were spiders, insect larvae, grasshoppers, and crickets (with an importance index of 51.4%). The total volume of food items consumed by males was greater than that consumed by females (P=0.028), and the volume of food items in the dry season was greater than in the rainy season (P=0.002). The rarefaction curves for prey category richness were higher in females than in males for both occurrence frequency and count of items.